MULTI-CRITERIA ASSESSMENT OF THE SEISMIC VULNERABILITY OF SCHOOL UNITS IN VASLUI CITY, ROMANIA - ANDRA-COSMINA ALBULESCU; Larion, Daniela; Grozavu, Adrian (WIT Transactions on Engineering Sciences, 2020)
In the context of an earthquake impact, school units are particularly vulnerable because of the specific age group of the population that studies there. This means that the earthquake mitigation strategies targeting schools should be carefully elaborated, starting from a proper assessment of their seismic vulnerability. Such assessments should be extensively conducted, especially in the case of urban settlements that are disadvantaged in terms of economic potential, social development and media image, like Vaslui City, Romania. This paper aims to evaluate the seismic vulnerability of school units in Vaslui City using a combination of Multi-Criteria Decision-Making (MCDM) methods and Geographic Information System (GIS) techniques. Unlike other assessments of this type, the proposed framework integrates both aspects related to the physical vulnerability of the school buildings, and social elements concerning the educational personnel, the age profile of the pupils, school hours and other factors. The methodology also includes a systemic vulnerability component that offers better insights about the access emergency services would have to the educational institutions in case of a powerful earthquake. The physical, social and systemic vulnerability factors/criteria are weighed via Analytic Hierarchy Process (AHP), while the 25 school units in the study area are evaluated using Weighted Product Model (WPM). The results are combined with GIS techniques in order to obtain a map that shows the seismic vulnerability level of the school units. The most vulnerable school units are the ones with tall old buildings located along narrow streets, with significant number of very young or disabled pupils. These findings represent the stepping stones for the retrofitting works and the educational programmes related to seismic hazards that should be implemented by local authorities. Although restricted by the low number of educational institutions in the study area, the proposed framework may be further on used in seismic vulnerability research.